How trade unions increase welfare - Alejandro Donado; Klaus Wälde (Center for Economic Studies and ifo Institute (CESifo), 2011)
Historically, worker movements have played a crucial role in making workplaces safer. Firms traditionally oppose better health standards. According to our interpretation, workplace safety is costly for firms but increases the average health of workers and thereby the aggregate labour supply. A laissez-faire approach in which firms set safety standards is suboptimal as workers are not fully informed of health risks associated with jobs. Safety standards set by better-informed trade unions are output and welfare increasing.
Keywords: J51; J81; 330; occupational health and safety; trade unions; welfare